PKM2-Induced the Phosphorylation of Histone H3 Contributes to EGF-Mediated PD-L1 Transcription in HCC - Wang, Xiao; Liang, Chao; Yao, Xin; Yang, Ruo-Han; Zhang, Zhan-Sheng; Liu, Fan-Ye; Li, Wen-Qi; Pei, Shu-Hua; Ma, Jing; Xie, Song-Qiang; Fang, Dong (Frontiers in Pharmacology, 2020)
High expression of PD-L1 in hepatocellular carcinoma cells usually inhibits the proliferation and functions of T cells, leading to immune suppression in tumor microenvironment. However, very little has been described regarding the mechanism of PD-L1 overexpression in HCC cells. In the present study, we found EGF stimulation promoted the expression of PD-L1 mRNA and protein in HCC cells. Inhibition of EGFR could reverse EGF-induced the expression of PD-L1 mRNA and protein. Subsequently, we also observed that the phosphorylation level of PKM2 at Ser37 site was also increased in response to EGF stimulation. Expression of a phosphorylation-mimic PKM2 S37D mutant stimulated PD-L1 expression as well as H3-Thr11 phosphorylation in HCC cells, while inhibition of PKM2 significantly blocked EGF-induced PD-L1 expression and H3-Thr11 phosphorylation. Furthermore, mutation of Thr11 of histone H3 into alanine abrogated EGF-induced mRNA and protein expression of PD-L1, ChIP assay also suggested that EGF treatment resulted in enhanced H3-Thr11 phosphorylation at the PD-L1 promoter. In a rat model of HCC, we found that the expression of phosphorylated EGFR, PKM2 nuclear expression, H3-Thr11 phosphorylation as well as PD-L1 mRNA was higher in the livers than that in normal rat livers. Taken together, our study suggested that PKM2-dependent histone H3-Thr11 phosphorylation was crucial for EGF-induced PD-L1 expression at transcriptional level in HCC. These findings may provide an alternative target for the treatment of hepatocellular carcinoma.